A Sociological Perspective on the Impact of Technology on Airport Management in Nigeria - Hyginus Obinna Ogbonna; Chidi Mba; Benedict Ibukun Ajayi; Bello Eugene (Richtmann Publishing, 2023)
This paper focuses on Sociological Perspective on the impact of technology on airport management, with focus on Nigeria. Its general aim is to ascertain the impact technology has on airport management; in particular: 1). To find out the implications advances in technology has on airport security management, 2). ascertain the implications of advances in technology on job retention for airport workers, 3). examine the impact of technology on airport users'experience, and 4) identify policy-based recommendations for a way forward. To achieve these objectives, the paper employed qualitative descriptive method; the use of tabulation, and graphic illustration in its analysis. For the sake of proper understanding, and with the aid of extrapolations, a Sociological theory, 'Functionalism', was adopted as the theoretical framework. In its expected outcomes, the study revealed the type of relationship between the two variables (technology and airport management), and the implications for Nigeria as a whole, and airport stakeholders in particular. A few of the findings include: technology has both positive and negative impact in Nigeria's airport management processes; it assures airport users'advantage, as well portends risk; it aids airport workers' workflow convenience, as well portends future job loss, etc. The paper therefore recommends, 1. Nigerian government should embrace the global advances in airport technology but at the same time brace up for its discontents; 2. Airport users should be technology-compliant to enable them appropriate the advantages of new airport technologies and manage its discontents as well; inter alia . Received: 6 October 2022 / Accepted: 27 December 2022 / Published: 5 January 2023